Evaluation of YouTube Audio Teaching Materials for Blind Students at SLB-A Beringin Bhakti - Rivanda Yuliani; Monica Astriyanti Sukardi (CV. Akademi Merdeka, 2024)
This study was conducted at Beringin Bhakti Special School (SLB) with the aim of evaluating the teaching media used by teachers during lessons. The research is titled